PENINGKATAN HASIL BELAJAR IPS MENGGUNAKAN MEDIA RODA BERPUTAR DI KELAS IV SDN 60/II MUARA BUNGO - Apdoludin Apdoludin; Reni Guswita; Berlian Tina Orlanda (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2022)
This research is motivated by student learning outcomes that do not meet the criteria for mastery learning, the application of varied, creative, innovative, and fun learning media in social studies learning, students in the class are still passive in the learning process, lack of mastery of social studies subject matter and average grades. for social studies subjects in class is still low. The solution to overcome these problems is to use a rotating wheel media. The location is in class IVBSDN 60/II Muara Bungo, Rimbo Tengah District, Bungo Regency, the method used in this research is CAR (Classroom Action Research).The results of the study showed that the learning process in the first cycle of implementation learning outcomes in the first cycle had a percentage of completeness at the first meeting 55.55% increased at the second meeting 61.11% increased, in the second cycle implementation at the first meeting 83.33% increased at the second meetingII 88.89%.The conclusion is that using the rotating wheel media for social studies learning can improve learning outcomes in IVB SDN 60/II.